Acid impregnated honeydew rind activated carbon for chromium and zinc removal - Mat Ali@Yunus, Zalilah Murni (2017)
Heavy metal contamination in aqueous media and industrial discharges are among the significant environmental problems, which have to be encountered due to the toxic nature and the accumulation of these metal ions in the food chains. This study has upcycled an agricultural waste namely honeydew rind (HOR) as a precursor in activated carbon (AC) adsorbent preparation using chemical activation process for Cr(IIl) and Zn(ll) removal from synthetic wastewater. Prior to the AC production, physicochemical characteristics of the HOR were analyzed by means of XRF, FESEM, TGA and FTIR. Optimization of sulfuric acid (H2SO4) and phosphoric acid (H3PO4) of 10%-30% v/v impregnation agent generated honeydew rind impregnated activated carbon (ACS) and honeydew rind impregnated activated carbon (ACP). Optimization of carbonization temperature involved temperature of 430°C-490°C for H2SO4 and 450°C-5 l0°C for H3PO4. Batch experiment study was conducted at constant value of 100 mL of synthetic wastewater, 125 rpm shaking rotation at ambient temperature. Brunauer-Emmet-Teller (BET), Langmuir and Freundlich were tested for isotherm adsorption while pseudo-first order and pseudosecond order were examined in kinetic behavior investigation. The column study was run under constant bed height, flow rate, inlet metal concentration of 25 cm, 16 mL/min, 1000 mL (Cr(lll)); 400 mg/L (Zn(II)) respectively at ambient temperature. Boehm titration indicated that ACS and ACP are classified as acidic AC. The highest iodine number value (528.63 mg/g) and BET surface area (591.25 m2/g) were obtained by 20% v/v ACS and carbonized at 470°C. The highest iodine number value (1174. 19 mg/g) and BET surface area (1272.38 m2/g) were achieved by 20% v/v ACP and carbonized at 490°C. Textural analysis produced an average pore diameter of 4.46 nm for-the ACS and 2.92 nm for the ACP respectively. Batch adsorption analysis resulted in an optimum condition occurring at pH 4.5, 0.1 g of ACS and ACP, 40 minute contact time and 1000mg/L for Cr(III) and pH 5.5, 0.1 g of ACS and ACP with a 40 min contact time and 400 mg/L for Zn(Il). Cr(III) maximum removal was 83.49% using ACS and 88.88%using ACP respectively while Zn(II) maximum removal was 8 I .55% using ACS and 84.13% using ACP respectively. It was demonstrated that high metal removal was achieved due to high range of metal concentration used in the study. Column adsorption demonstrated breakthrough of 70 min and 100 min for Cr(III) and Zn(II), respectively. The regeneration study achieved three (3) adsorption cycles of the spent ACP. The present study was able to prove that the honeydew rind impregnated activated carbon is a promising adsorbent in Cr(Ill) and Zn(Il) removal from synthetic wastewater solution. This study has also therefore confirmed that a relatively lower heating rate in the course of carbonization may manage to convert the HDR into its AC. Ion exchange and complexation were suggested to be the metals sorption mechanism.